Using the 12-item short form health survey (SF-12) to assess self rated health of an engaged population impacted by hurricane Harvey, Houston, TX - Garett T. Sansom; Katie Kirsch; Jennifer A. Horney (BMC, 2020)
Abstract Background In the last decade there has been an increase in community-based organizations providing support and educational outreach to populations effected by hazards. Prior research has demonstrated various roles that community social capital can play in both the enhancement of disaster preparedness and the mitigation of physical and mental health impacts following a natural disaster. Methods To assess self-reported health of residents of South Houston, Texas impacted by Hurricane Harvey, attendees of a community event completed a survey that included the 12 item short form health survey version 2 (SF-12v2). Results Although survey participants were older and more likely to be African-American than the overall population of Houston, they had higher mental health composite scores that the national average, with increases in mental wellbeing associated with a longer length of residence in their neighborhood. Conclusions The City of Houston, with highly segregated, socially vulnerable populations at high risk from natural hazards, should consider ways to support community engagement around disaster preparedness, response, and recovery that may build community cohesion and improve post-disaster mental health.